Anais Dos Workshops Do VIII Congresso Brasileiro De Informática Na Educação (CBIE 2019) 2019
DOI: 10.5753/cbie.wcbie.2019.833
|View full text |Cite
|
Sign up to set email alerts
|

A Evolução da Área de Busca como um Processo de Aprendizagem com base em um Mapeamento Sistemático

Abstract: Search as Learning (SaL) states that search engines must support users through ways to learn during the search process. Previous studies were responsible to propose SaL as a research agenda, carrying different perspectives of investigation and research challenges to be overcome. This paper presents an overview of this research area from an analysis of the publications. We selected 62 papers in which we sought to identify the main authors, the timeline of publications and the main research topics. We believe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Finally, Machado et al (2019) present a meta-analysis of the evolution of the SAL agenda based on the publications. They identify the main authors, the timeline of publications and the main research topics.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Machado et al (2019) present a meta-analysis of the evolution of the SAL agenda based on the publications. They identify the main authors, the timeline of publications and the main research topics.…”
Section: Related Workmentioning
confidence: 99%
“…Searching as Learning (SAL) exploits the synergy between searching and learning, focusing on the impact, influence, and consequences of using search engines as learning technologies (Machado et al, 2019). Studies of this area argue that although search engines are widely used for learning-oriented information needs, they are optimized primarily for generic relevance, not for effective learning, nor do they consider learning as an incremental process of knowledge acquisition (Gwizdka et al, 2016, Syed andCollins-Thompson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Searching as Learning (SAL) is a recent research area that considers issues involving learning during the search process (Moraes et al, 2018). It focuses on the impact, influence, and consequences of using search engines as learning technologies (Machado et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Marchionini (2018) reviewed historical aspects of the learning literature, giving attention to learning theories and highlighting changes that occur on neural, cognitive, affective, and behavioral dimensions. Machado et al (2019) revealed the presence of few studies rooted in learning theories in SAL, which may represent a research gap. SAL is an approach that suits better for informal learning perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Desde a intenc ¸ão de se buscar uma informac ¸ão como aprendizado até o momento que se obtém o conhecimento desejado, acontece um processo de aprendizagem com a busca [Machado et al 2019]. Searching as Learning (SaL) é a área que visa investigar a profunda relac ¸ão entre o processo de busca e a aprendizagem [Vakkari 2016].…”
unclassified